Thrombolytic protease characterization from leaves and fruit flesh of the jernang rattan plant (Daemonorops draco) - Urbanus Yustus Lebuan; Roga Florida Kembaren; Merry Meryam Martgrita; Cut Rizlani Kholibrina (Indonesian Journal of Biotechnology, 2023)
Thrombolytic agents are used for thrombolytic therapy to dissolve blood clots that form in a blood vessel. All currently used thrombolytic agents have unfavorable shortcomings, such as gastrointestinal bleeding, allergic reactions, and thrombolytic agent resistance, treatment for some of which can be quite expensive. As a result, the search for thrombolytic agents derived from plants is currently taking place. Some plants have been discovered to contain protease enzymes with thrombolytic activity; pharmaceuticals derived from plants are believed to be safer. Jernang rattan (Daemonorops draco) is a plant of the Arecaceae family and is known to produce resin. Jernang rattan resin is also known to have antioxidant, antiseptic, antitumor, antimicrobial, and cytotoxic activity, but very limited information on proteolytic activity of the protease from this plant. This research aims to isolate proteases from the leaves and fruit flesh of the rattan jernang plant (D. draco) and to investigate the proteolytic activity of the isolated proteases. The protease was isolated from the leaves and the fruit flesh, and then partially purified by ammonium sulfate precipitation. The radial caseinolytic assay showed that protease in a 60% ammonium sulfate fraction gave a clear zone, with diameters of 1.4 cm and 1.8 cm for the protease isolated from leaves and fruit flesh, respectively. A Folin‐Ciocalteau assay showed that the enzymes isolated were able to hydrolyze casein and release L‐tyrosine, with activity of 0.158 U/mL and 0.174 U/mL for the protease from the leaves and fruit flesh, respectively. A fibrinogenolytic assay showed that the protease from the fruit flesh hydrolyzed the A‐α, B‐β and the γ chain of human fibrinogen, while the protease from the leaves hydrolyzed the A‐α and γ chain. Both proteases were inhibited by 56% by phenylmethylsulfonyl fluoride (PMSF), indicating that the enzymes are serine proteases. Based on the assay results obtained, it can be concluded that proteases isolated from the leaves and fruit flesh have potential as thrombolytic proteases.